2011
DOI: 10.4028/www.scientific.net/amr.378-379.453
|View full text |Cite
|
Sign up to set email alerts
|

Study on Limestone Uniaxial Compression Creep Test with Chemistry–Mechanics Coupling Action

Abstract: Considering the erosion effect of underground water deteriorate the micro structure of rock which results in the time effect of rock deform, the paper developed a uniaxial compression equipment for rock creep under chemical and stress coupling action. It adopts good corrosion prevention design, can conveniently test the rock uniaxial compression creep effect with erosion. Take limestone as study object, the paper carried out uniaxial compression creep tests with different PH environment. Compared the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Yang Yu et al reported a decrease in pH, an increase in dissolution time, an increase in cracking and a decrease in peak strength (Yu et al 2023). Consequently, limestone exhibits an obvious creep effect in acidic solution, and the lower the pH is, the greater the creep deformation (Jiang et al 2012). Dissolution affects the failure mode of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Yang Yu et al reported a decrease in pH, an increase in dissolution time, an increase in cracking and a decrease in peak strength (Yu et al 2023). Consequently, limestone exhibits an obvious creep effect in acidic solution, and the lower the pH is, the greater the creep deformation (Jiang et al 2012). Dissolution affects the failure mode of the sample.…”
Section: Introductionmentioning
confidence: 99%